Hydrogen production, storage, and utilization technologies and applications - Tcharkhtchi, Abbas; Vanaei, Hamid Reza; Lucas, Albert; Farzaneh, Sedigheh (Emerging materials and technologies, 2025)
Hydrogen Production, Storage, and Utilization: Technologies and Applications presents a comprehensive and in-depth exploration of the scientific and engineering principles of hydrogen technology. Written in a technical and scientific manner, using rigorous scientific language and mathematical models to explain principles and applications, the book covers various aspects of hydrogen technology, ranging from fundamental principles of thermodynamics and kinetics to practical applications of hydrogen production, storage, and utilization.- Includes chapters on the latest advances in hydrogen production, including methods such as steam methane reforming, electrolysis, and biomass gasification- Expresses the scientific principles of hydrogen storage, including metal hydrides, carbon-based materials, and liquid carriers- Discusses the latest research on fuel cell technologies, including proton-exchange membrane fuel cells, solid oxide fuel cells, and microbial fuel cells- Covers hydrogen safety aspects, including risk assessment, safety protocols, and safety standards- Explores the challenges and opportunities associated with the deployment of hydrogen technology, including economic viability, environmental impact, and social acceptanceThe book is intended for scientists, engineers, researchers, and graduate students in the fields of chemical engineering, materials science, renewable energy, and sustainability, as well as policymakers and stakeholders interested in the potential of hydrogen as a clean and renewable energy carrier